Anti‐Corrosion for Reversible Zinc Anode via a Hydrophobic Interface in Aqueous Zinc Batteries (Adv. Energy Mater. 9/2022). Issue 9 (3rd March 2022) - Guan, Kailin; Tao, Li; Yang, Rong; Zhang, Haonan; Wang, Nengze; Wan, Houzhao; Cui, Jian; Zhang, Jun; Wang, Hanbin; Wang, Hao
Abstract : Aqueous Zinc Batteries The study of the reversible zinc metal anode is significant in the context of energy storage in aqueous zinc batteries. In article number 2103557, Li Tao, Jian Cui, Hao Wang and co‐authors report the use of quaternary ammonium cationic surfactants as aqueous electrolyte additives forming a self‐consistent hydrophobic interface to block corrosion by water and modulate zinc deposition.